The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/healthcare9070826
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Job Engagement on the Quality of Nursing Services: The Effect of Person-Centered Nursing in South Korean Nurses

Abstract: Nurses’ job engagement could help improve the quality of nursing services, and person-centered nursing is expected to play an important role in this relationship. However, little is known about the role of person-centered nursing in the association between job engagement and quality of nursing services. This study examines the moderating and mediating effects of person-centered nursing on the relationship between the job engagement and the quality of nursing services in Korean nurses. In October 2020, 200 hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…This can lead to increased job satisfaction and a higher overall sense of fulfillment in their professional role. When nurses are satisfied with their work, they are more likely to be motivated, engaged, and committed to providing high-quality care [ 50 , 51 ]. In contrast, the use of mechanical assistance in patient care might affect the interpersonal dynamics between nurses and patients.…”
Section: Search Strategymentioning
confidence: 99%
“…This can lead to increased job satisfaction and a higher overall sense of fulfillment in their professional role. When nurses are satisfied with their work, they are more likely to be motivated, engaged, and committed to providing high-quality care [ 50 , 51 ]. In contrast, the use of mechanical assistance in patient care might affect the interpersonal dynamics between nurses and patients.…”
Section: Search Strategymentioning
confidence: 99%
“…Additionally, research like that conducted by Kim and Seo [5] highlights the importance of elements like person-centred nursing and work engagement in determining the calibre of nursing services. The association between work engagement and nursing service quality was found to be mediated and moderated by person-centred nursing, indicating that approaches that prioritise individualised care can improve the quality of nursing care.…”
Section: Introductionmentioning
confidence: 99%
“…In many professions, particularly healthcare, the relationship between job satisfaction and high-performance work systems (HPWS) is critical. Studies show that HPWS has a favourable correlation with both overall employee satisfaction [8], and work satisfaction among medical staff [5]. Further research has revealed that HPWS influences the perception of job success through employability orientation and HPWS attribution [9].…”
Section: Introductionmentioning
confidence: 99%
“…Work engagement has a positive effect on nurses’ physical and mental health and career development, enhancing job satisfaction, improving job performance and productivity, and reducing absenteeism and turnover intentions ( Simone et al, 2018 ; Giménez-Espert et al, 2020 ). Meanwhile, with a high level of work engagement, nurses are also energetic and committed at work, compassionate to patients, and do their best to help patients relieve pain, which improves the quality of care and organizational performance ( Brubakk et al, 2019 ; Kim and Seo, 2021 ). As nurses are more important professionals in the field of health care, the improvement of the quality of hospital nursing services is closely related to the level of nurses’ work engagement.…”
Section: Introductionmentioning
confidence: 99%